Evolution of mathematical concepts: An elementary study - Wilder, Raymond L. (Englans Open University Press, 1973)
A prominent educator offers a unique exploration of modern mathematics' evolutionary development. Rather than conducting a survey of the history or philosophy of mathematics, the author envisions mathematics as a broad cultural phenomenon. His treatment examines and illustrates how such concepts as number and length were affected by historic and social events.
Keywords: Mathematics philosophy; Mathematics; Mathematics history